State of Mental Health of the Children in Child Welfare Centers in Batticaloa District - Genoosha, N.; Arulpragasam, A.N.; Gadambanathan, T.; Karthijekan, K. (University of Jaffna, 2022)
Children under institutionalised care are vulnerable to develop mental health abnormalities. This study aimed to assess the mental health of the children in child welfare centers and identify the influencing factors. A cross-sectional descriptive study was conducted in 30 child welfare centers in Batticaloa district from January 2017 to December 2019. A total of 647 children aged from 11 to 17 years were recruited. The self-reported youth version of strengths and difficulties questionnaire was used to assess the children’s mental health. Multiple linear regression stepwise method analyses were employed to identify the factors influencing the children’s mental health. The mean scores of the total difficulties, emotional problems, conduct problems, hyperactivity, peer problems and prosocial behaviour were 12.22±5.18, 4.14±2.09, 2.45±1.67, 3.27±1.77, 2.36±1.76 and 8.43±1.51, respectively. Fifty-two (8.0%) children had an abnormality in total difficulties, 73 (11.3%) had emotional problems, 89 (13.8%) had conduct problems, 22 (3.4%) had hyperactivity, 34 (5.3%) had peer problems, and 7 (1.1%) had abnormal prosocial concerns. Poor mental health was statistically associated with the presence of feeling of distress (p<0.001), family history of mental illness (p=0.001), female gender (p=0.002), poor satisfaction of family interaction (p=0.008), and poor academic performances (p=0.034). Forty-five children found with abnormal mental health in the screening were referred to the child mental health clinic at Teaching Hospital Batticaloa; only sixteen attended the clinic, and six were diagnosed with Childhood psychiatric disorders. The majority of the children in child welfare centers are mentally healthy, and few children exhibit abnormal mental health. Therefore, approaches to support the children in maintaining optimum mental health are valuable in their development. Further, early screening and referrals must be enhanced to prevent adversities
Keywords: Mental health; Children; Child Welfare Centers; Institutionalised care; Strengths; Difficulties questionnaire